The Ways of Using Recycling Process during Lesson and the Importance of It - Kenjayeva Nigora Uktamovna (Researchparks Publishing, 2022)
This article deals with the significance of recycling within the lesson and how to conduct effective classroom activities with the help of the recycling process. As this allows predicting pedagogical strong points of each teacher as well as teaching students according to various approaches in an appropriate way. This article includes the best way of building recycling opportunities for educational purposes during a language lesson by using the same language in different, diverse activities, using the PPP model (Presentation – Practice - Production).